Development of Computer Catalogue at Indian Statistical Institute, Bangalore Centre Library - Krishnamurthy, M. (Journal of Information and Knowledge, 2001)
Describes the development of computer catalogue undertaken at Indian Statistical Institute’s Bangalore Center Library, in which range of professional techniques were applied to modernize the library with the objective of improving its services and raising its profile with in the institution. This involved thorough stock revision, retro conversion of the catalogue, and introduction of an integrated automated library management system.